The Mitochondrial tRNAPhe 625G>A Mutation in Three Han Chinese Families With Cholecystolithiasis - Hou, Lingling; Hu, Cuifang; Ji, Lili; Wang, Qiongdan; Liang, Min (Frontiers in Genetics, 2022)
In this study, we assessed three Chinese families with inherited cholecystolithiasis and conducted the clinical, genetic and molecular characterization of these subjects. 8 of 18 matrilineal relatives had a clinical phenotype in these three families. Sequence analysis of complete mitochondrial genomes in these probands identified the homoplasmic tRNAPhe 625 G>A mutation, and distinct sets of mtDNA polymorphisms belonging to haplogroups H2, F4b, M10a.The 625G>A mutation disturbed the classic G-C base-pairings at a highly conserved position 49 in the T-stem of mitochondrial tRNAs. Molecular dynamics simulation shown that the structure of tRNAphe with 625 G>A mutation was noticeably remodeled while compared with the isoform of the wild-type. The occurrence of tRNAPhe 625 G>A mutation in these several genetically unrelated subjects strongly indicates that this mutation is involved in the pathogenesis of cholecystolithiasis. This is the first evidence that tRNA mutations are associated with cholecystolithiasis, and it provided more insights for the genetic mechanism of cholecystolithiasis.